Evaluation of serum Calcium level in psoriatic patients - Jomah, Noura Shokri; Ismaiel, Mohamad Adel; Khadam, Jamal (Journal of medical and pharmaceutical sciences, 2022)
Background: Psoriasis is a chronic immune- mediated skin disease, with a genetic predisposition. Many factors can trigger or exacerbate psoriasis. Recently, some studies found that psoriasis was associated with hypocalcemia. So we did this study to find this association in our patients.Objective: To evaluate serum calcium level in psoriatic patients and compare it with controls.Methods: This case- control study included 160 subjects (80 patients with psoriasis and 80 controls) admitted to dermatology clinic at Tishreen University Hospital, Latakia, Syria, from 2020- 2021. Serum calcium and serum albumin levels were estimated in all patients.Results: Calcium levels were significantly lower in psoriatic patients than in the control group (mean = 8.98±0.5 in patients vs 9.48±0.5 in controls, p- value
Keywords: psoriasis; hypocalcemia; calcium; serum level; PASI score